Dactoscopy in human identification: A retrospective study in Bhubaneswar City - S Bhuvaneshwari; Shreetapa Chand; Dipak Chaudhari; Balaji Manohar; Lipsa Buyan; Soundarya Srinivasan (Journal of Pharmacy and Bioallied Sciences, 2023)
Anthropometry, fingerprints, age estimation, gender determination, blood types, DNA, and dental features are examples of traditional techniques for identifying a person. The present study aimed toward observing the patterns of fingerprints and their reliability toward human identification. A retrospective study was conducted in a tertiary care unit in Bhubaneswar city. Fingerprints were recorded, and the individual identification mark was noted for each individual. Reporting of the patterns was done. Sir Henry Galton's classification was used to study the fingerprint patterns. IBM Statistical Package for Social Sciences was used for the statistical analysis. Type A was the most common type seen for the right-hand little finger. Type A was the most common type seen for the left-hand little finger; Type C was the most common type seen for the left-hand ring finger. Statistically significant correlations between gender and dermatoglyphics were found, supporting their usage as trustworthy forensic evidence.